The factors to be considered by the competition authorities when a fine may cause the firm to exit - Quilliam, Layne Edwin (Rhodes University, Faculty of Law, Law)
The Competition Act empowers the Competition Tribunal to levy fines against a firm for certain contraventions of the Act. Such fines are statutorily capped to prevent the fine from causing the firm's exit. This maximum is based on the overarching principle of fairness which precludes a fine, on its own, from destroying a firm's business. However, the Competition Appeal Court acknowledged in 2013 that fines below this cap may still cause a firm to exit. The purpose of this paper is to propose the factors that should be considered when determining a firm's ability to pay such a below-cap fine. These factors are the calculation of the fine, probable exit, causation of exit and the competitive effect of the firm's exit. The fining provisions of the Act are initially explored to provide context for the discussion and are then compared to equivalent provisions in Europe. Liquidation and business rescue proceedings are then described as the most common forms of a firm's exit from the market. Methods for determining the causal relationship between the fine and the firm's exit are explored through delictual law's factual and legal causation. The competitive effects of the firm's exit are premised on the purpose of the Competition Act and are evaluated through the Competition Act's merger provisions, specifically, the failing firm factor. These proposed factors are then tested through hypothetical facts to analyse their possible interactions and efficacy.
Keywords: South Africa. Competition Act, 1998; Competition Tribunal (South Africa); Business enterprises Law and legislation -- South Africa; Debt-to-equity ratio -- South Africa; Bankruptcy Prevention; Causation; Competition